145 EDITH (EMERGENCY DEPARTMENT IN THE HOME): FACTORS THAT INFLUENCE CONVEYANCE RATES TO HOSPITAL. (18th November 2021) - Davis, A J; Doyle, C; Dhonaill, R N; Nally, S M; Namara, R M
Abstract: Background: The EDITH team has provided an alternative care pathway for older adults in need of emergency services. Patients are attended to by a doctor and Occupational Therapist in their own home as an alternative to an emergency department presentation. The conveyance rate for transfers to hospital is 7.2% of total patients treated by the EDITH service. It is imperative to identify this patient group and look for commonalities in same. This assists with service planning and also identifies high risk patients who may need transfer to hospital; thus ensuring patients are prioritised appropriately within the service. Methods: Following an audit of a subsample (n = 230) of the entire EDITH patient population (3, 137 patients), 26 patients were transferred to hospital. Analysis of the Health Care Record was completed to identify similarities in this population group and compare same with the 'typical patient profile'. Results: It was found that 38% of patients had a recent ED presentation (in the past month) and 31% had a prolonged hospital stay (> 2 weeks in past year). 57% had a documented change in functional baseline over past 2 weeks. 46% of patients were transferred to level 4 acute hospitals for medical follow up and 54% were transferred to level 3 hospitals or rehabilitation facilities for MDT input. 77% of patients had a Clinical Frailty Scale score of 6 and above (moderately frail) compared with 62% of the non-conveyance population. Presenting complaints included: falls 35%, respiratory issues 12%, pain management 12%, gastrointestinal issues 12%. Conclusion: Risk factors for conveyance to hospital for EDITH patients have been identified. This knowledge can potentially be used to triage patients and ensure timely review from EDITH for this high risk patient group.